Molecular cloning of mRNA sequences for cardiac alpha- and beta-form myosin heavy chains: expression in ventricles of normal, hypothyroid, and thyrotoxic rabbits. - Sinha, A M (1982)
We have isolated cDNA clones from thyrotoxic (pMHC alpha) and normal (pMHC beta) adult rabbit hearts. Restriction map analysis and DNA sequence analyses show that, although there is strong homology between overlapping regions of the two clones, they are distinctly different. The two clones exhibited 78-83% homology between the derived amino acid sequences and those determined by direct amino acid sequence analysis of rabbit fast skeletal muscle myosin heavy chains. The clones specify a segment of the myosin heavy chain corresponding to subfragment 2 and the COOH-terminal portions of subfragment 1. Nuclease S1 mapping was used to compare transcription of the two clones with expression of the alpha and beta forms of myosin heavy chains in the ventricles of thyrotoxic, hypothyroid (propylthiouracil-treated), and normal rabbits. Thyrotoxic ventricles contained only pMHC alpha transcripts whereas hypothyroid ventricles contained exclusively pMHC beta transcripts. These data correlate well with the presence of alpha- and beta-form myosin heavy chains. In the normal young adult rabbit, pMHC beta transcripts predominate, agreeing with the known beta form/alpha form ratio of 4:1. We therefore conclude that pMHC alpha and pMHC beta contain sequences of the alpha- and beta-form myosin heavy chain genes, respectively.